BRIDGING THE ACADEMIA-INDUSTRY GAP: A STAKEHOLDER FRAMEWORK FOR INTERNSHIP IN ENGINEERING EDUCATION - Dr. Amol Dapkekar, Dr. Neeta Patil (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
India possesses one of the largest and most qualified young workforces in the world, with a significant portion of the youth actively preparing for employment in the industrial sector. Internships serve as a critical bridge between academic learning and industry practices, offering students valuable exposure to real-world work environments and an opportunity to develop practical skills. For aspiring engineers, internships are not merely optional experiences but essential tools for skill enhancement and for improving employability in core industries. However, many private engineering institutions often neglect to promote or facilitate internships effectively, leading to a noticeable decline in placement outcomes. On the other hand, interns themselves sometimes fail to leverage these opportunities to apply their academic knowledge meaningfully, thereby limiting their potential to secure job offers. Furthermore, while industry stakeholders express interest in hiring fresh engineering talent, they often remain hesitant or restrictive when it comes to offering structured internship opportunities. This study explores the critical role of internships in enhancing core sector placements among engineering graduates and, by extension, in contributing to India’s economic development. Anchored in the context of AICTE’s guidelines on mandatory internships in engineering education, the paper examines the responsibilities and contributions expected from students, academic institutions, and industry. It emphasizes the need for collaborative engagement among these stakeholders to transform internships into effective pathways for successful recruitment.